PENGEMBANGAN PERANGKAT PEMBELAJARAN FISIKA PADA MATERI GERAK LURUS YANG BERORIENTASI PADA PEMBELAJARAN AKTIF DENGAN STRATEGI TURNAMEN BELAJAR DI SMA NEGERI 3 LAMONGAN - Haryono, Heny Ekawati (saintis, 2016)
This study was aimed to develop a learning device oriented active learning strategies learning tournament on the material straight motion for class X SMA. The development of this learning device refered to a development model suggested by Thiagrajan, Semmel ie 4-D models with each step included in the revision activity. Activities revision aimed to produce a decent learning device in terms of validation and implementation. The purpose of this study to describe the application of the device was seen from the results of learning activities, learning outcomes mastery, student responses, and also obstacles during the learning process. Based on the results of the analysis can be concluded that learning-oriented devices on active learning to learn tournament strategy developed could be said to be feasible in terms of validation and implementation. The results of feasibility validation device consisted of a syllabus, lesson plans, worksheets, Student Book and Instrument Ratings. The validation of the results showed that the learning device deserves to be tested on a limited basis to determine the feasibility of implementation. Limited trial conducted at SMA Negeri 3 Lamongan X-7. The result of the application of the device during the tests showed the implementation of RPP by 96%, achieving the studentsâ learning outcomes classical completeness of 87.5% and studentsâ responses indicated a positive result 88% agree with the activities and learning devices with active learning orientation.